The great train robbery [videorecording (DVD)]. - Crichton, Michael, 1942-2008; Connery, Sean; Sutherland, Donald, 1935-; Down, Lesley-Anne (MGM Home Entertainment, 1998)
A recreation of the dramatic 19th century train robbery masterminded by Edward Pierce. He was the first man in history to rob a moving train, and he and his accomplices got away with a fortune in gold.